Effects of gadolinium chloride and glycine on hepatic and pancreatic tissue damage in alcoholic pancreatitis - Schneider, Lutz; Hackert, Thilo; Longerich, Thomas; Hartwig, Werner; Fritz, Stefan; Krych, Ralf; Fortunato, Franco; Gebhard, Martha-Maria; Werner, Jens (Pancreas, 2010)
Systemic complications in alcoholic pancreatitis are supposed to be aggravated by inflammatory liver damage. Resident macrophages including hepatic Kupffer cells play a pivotal role in mediating systemic complications in severe necrotizing pancreatitis (SNP). The aim of this study was to evaluate the effects of Kupffer cell inhibition on the inflammatory liver damage in experimental alcoholic pancreatitis.
Gesehen am 21.06.2023